2020
DOI: 10.1007/s00403-020-02116-8
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and insecure attachment predict disability and quality of life in psoriasis independently from disease severity

Abstract: Psoriasis is a multisystemic inflammatory disease with a significant burden in terms of disability and reduced quality of life. The interrelations between disease severity, psychological well-being, and disability and/or health-related quality of life (HRQOL) of psoriatic patients are not fully understood. The aim of the study was to assess the relative role of disease severity, depressive symptoms, and insecure attachment in predicting disability and HRQOL in 105 patients with psoriasis. Objective measures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…In last years, the concept of psoriatic disease has been developed thanks to a better understanding of molecular pathogenetic mechanisms leading to psoriasis (PSO) and associated musculoskeletal manifestations [ 1 ]. PSO is a common chronic skin inflammatory condition associated with quality-of-life impairment and disability [ 2 , 3 ]. The disease presents cutaneous manifestation as erythematous and scaling plaques with prototypical distribution in plaque-type PSO, but also rarer and severe variants, such as pustular and erythrodermic PSO and special localization such as nails, genitals, skin folds, and palmo-plantar areas [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In last years, the concept of psoriatic disease has been developed thanks to a better understanding of molecular pathogenetic mechanisms leading to psoriasis (PSO) and associated musculoskeletal manifestations [ 1 ]. PSO is a common chronic skin inflammatory condition associated with quality-of-life impairment and disability [ 2 , 3 ]. The disease presents cutaneous manifestation as erythematous and scaling plaques with prototypical distribution in plaque-type PSO, but also rarer and severe variants, such as pustular and erythrodermic PSO and special localization such as nails, genitals, skin folds, and palmo-plantar areas [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Különböző tanulmányokban vizsgálták bizonyos bőrbetegségeknél a bőrgyógyászati életminőség szintje és a kötődési jellemzők közötti kapcsolatokat. Az életminőség alacsony szintjével kapcsolódtak össze egyes bizonytalan kötődési stílusok jegyei pikkelysömörös (Esposito et al, 2020), krónikus csalánkiütéses (Barbosa et al, 2011) és atópiás dermatitiszes (Dieris-Hirche et al, 2012) pácienseknél. c) Megküzdés a bőrbetegséggel.…”
Section: Pszichológiai Tényezôk Bôrbetegségeknélunclassified
“…In the study by Esposito [ 34 ], the attachment style was studied in 105 patients with psoriasis, and it was found that the worried (anxious) attachment style is a predictor of a higher level of disability and worse quality of life. In these psoriatic patients, a therapeutic intervention targeting dysfunctional attachment may be useful.…”
Section: Introductionmentioning
confidence: 99%